Organic solutes in forage sorghum genotypes under saline stress - Alves Oliveira, Lucimauro Antonio Alves; Barreto, Levy Paes; Neto, Egídio Bezerra; Santos, Mércia Virgínia Ferreira dos; Costa, Jordânia de Cássia Araújo (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the organic compound content in forage sorghum under salt stress condition. The experiment was carried out in a greenhouse with a factorial scheme of 3x10, in a completely randomized design and four replicates. The evaluated treatments were three levels of soil salinity (2.4, 10 e 16 dS m-1) and ten genotypes of forage sorghum (IPA SF-25, IPA 02-03-01, IPA 42-70-02, CSF-4, CSF-5, CSF-6, CSF-7, CSF-8, CSF-9 e CSF-10). There was an increase of 20.2 and 21.3% in soluble carbohydrates, respectively, for salt treatments of 10 and 16 dS m-1. The content of soluble proteins varied among sorghum cultivars, as a response to salt treatment. The highest values of total free amino acids occurred in plants grown under the salinity level of 16 dS m-1. Saline treatments increased sorghum content of proline for the genotypes CSF-5, CSF-6 and CSF-9 (at 10 dS m-1), and for CSF-10 and CSF-4 (at 16 dS m-1). The increase in soluble carbohydrates, soluble proteins, total free amino acids and free proline content is proportional to soil salinity and varies with the studied genotypes.